Revitalisasi dan Rancang Kota: Beberapa Catatan dan Konsep Penataan Kawasan Kota Berkelanjutan - Martokusumo, Widjaja (Journal of Regional and City Planning, 2006)
Urban development with its complexity is a permanent process of adjustment towards economic use of technology and development of socio-culture patterns. Changes due to globalization and modernization require a sensitive understanding in the way how people manage critical, and irreplaceable existing urban resources properly. Nowadays, this is clearly indicated by the emerging issues of sustainability and depletion of valuable resources in the discourse on urban design and development. In course of transformation process revitalization can be perceived as one of urban strategies. In essence, revitalization is an integrated effort to bring back the vitality of underused and deteriorated urban areas. The scope of revitalization is economic, socio-cultural and physical criteria for new investments, while the non-physical interventions, mostly dominated by economic and financial considerations, social rehabilitation etc., strive for sustainability of urban area. Basically, revitalization efforts try to enhance economic development, in such a way that maintenance and significant characteristics of a place will be guaranteed. This, urban revitalization efforts must be based on a comprehensive understanding of history, meaning and locality. Due to complexities of current urban problems urban design as this paper argues, is more than just physical design. While revitalization of urban quarters aims for renewal of economic use, urban design on the other hand plays an important role in shaping and giving directions on physical intervention in urban fabrics.